Anistia e cumprimento das obrigações tributárias no Estado do Ceará - Silva, Paulo Wirisson Melo e (2019)
This paper investigates the value of the loss in financial value and the impacts of the systematic Tax Refinancing concession practiced by the State of Ceará in the years 2009, 2013, 2014 and 2015. In particular, it is assessed if this policy causes a symptomatic situation of not compliance with tax obligations by the taxpayer. For this purpose, the asset valuation technique is used to evaluate the financial loss resulting from the non-receipt of tax obligations and econometric models to measure the impact of refinancing measures (REFIS) on future ICMS tax collection. Analyzing the obtained results, it is observed that the realization of Refis in short periods does not stimulate the payment of Infraction Taxes, an impact that is only significant 5 years after the realization of the first Refis. In addition, the disclosure of the performance of Refis negatively impacts the collection and accumulation of debt. In the financial analysis it is verified that even the amounts received in Refis cause financial loss of 38.6% after 5 years.